2012
DOI: 10.1021/am3021069
|View full text |Cite
|
Sign up to set email alerts
|

Ferroferric Oxide/Multiwalled Carbon Nanotube vs Polyaniline/Ferroferric Oxide/Multiwalled Carbon Nanotube Multiheterostructures for Highly Effective Microwave Absorption

Abstract: Light-weight nanocomposites filled with carbon nanotubes (CNTs) are developed for their significant potentials in electromagnetic shielding and attenuation for wide applications in electronics, communication devices, and specific parts in aircrafts and vehicles. Specifically, the introduction of a second phase into/onto CNTs for achieving CNT-based heterostructures has been widely pursued due to the enhancement in either dielectric loss or magnetic loss. In this work, ferroferric oxide (Fe(3)O(4)) was selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
363
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 847 publications
(379 citation statements)
references
References 41 publications
7
363
2
Order By: Relevance
“…56). Cao et al 73 reported a broad band absorber with MWCNTs/Fe 3 O 4 nanocomposites and concluded that the interface introduced by Fe 3 O 4 generated resonance in complex permittivity and permeability as well as sufficiently enhanced magnetic loss resulted in enhancing microwave absorption performance and widening effective absorption BW. In Table II the results of RLmax, bandwidth and matching frequency for epoxy composites filled with magnetic and dielectric (MWCNTs) nano fillers are summarized.…”
Section: 72-18mentioning
confidence: 99%
“…56). Cao et al 73 reported a broad band absorber with MWCNTs/Fe 3 O 4 nanocomposites and concluded that the interface introduced by Fe 3 O 4 generated resonance in complex permittivity and permeability as well as sufficiently enhanced magnetic loss resulted in enhancing microwave absorption performance and widening effective absorption BW. In Table II the results of RLmax, bandwidth and matching frequency for epoxy composites filled with magnetic and dielectric (MWCNTs) nano fillers are summarized.…”
Section: 72-18mentioning
confidence: 99%
“…Various carbon materials, e.g., carbon nanotubes (CNTs), carbon nanofi bers (CNF), carbon nanocoils, and mesoporous carbon, have been utilized to construct highly effective microwave absorbers in the past decades. [6][7][8][9][10][11][12] Although these carbon-based materials have made signifi cant progress in the fi eld of microwave absorption, some elaborate innovations on structure and components are still paving the way for exciting performance to satisfy the requirements of practical applications.Recently, graphene appeared as a fascinating material and grabbed worldwide attention, whose unprecedented physical and chemical properties derived from its unique 2D structure have promised great potential in many research fi elds. [ 13 ] Notably, high charge carrier mobility, extraordinary electrical and thermal conductivity also rendered graphene as a new microwave absorber, and it was found that reduced graphene oxide (rGO) provided superior microwave absorption to graphene oxide (GO).…”
mentioning
confidence: 99%
“…It was found that the Fe 3 O 4 /MWCNT composites demonstrate excellent microwave absorption performance with wide absorption bandwidth due to the combined contribution of dielectric and magnetic loss. And the reflection loss peak achieves up to 40 dB (3 mm in thickness), much more effective than that of naked CNT and ferrite [16].…”
Section: Introductionmentioning
confidence: 96%